What Makes North Kalimantan Residents Take Housing Loans? - Budianto Oky Prasetya (Jurnal Ilmu Ekonomi Terapan, 2023)
Housing is one of the human needs that must be met. Many ways are used to get the required residence (house). One of them is by taking a housing loan. Various factors can become obstacles in taking housing loans. This study used logistic regression – Logit and took a sample of 514 households in North Kalimantan Province. This research will examine the influence of economic, social, demographic, and geographic factors in household decisions to take housing loans. The results showed that household income, interest rates, HOH employment status, HOH age, and household location had a significant positive effect. In contrast, income per capita and marital status had a significant negative effect. Meanwhile, the number of HM working had no significant effect. Of the variables used, the household location variable influences a household's decision to take housing loans with an OR of 3.62.